Eksistensi Peran Serikat Buruh dalam Upaya Memperjuangkan Hak Upah Pekerja: (Dalam Penetapan Upah Minimum) - Ismi Pratiwi Podungge (Jurnal Hukum Lex Generalis, 2020)
Employees have the ultimate goal of doing their jobs as one of the vital stakeholders supporting the economy. Not only to serve the country but also as an effort to meet various needs of life. But in fact, often employers are not fully able to provide proper welfare. Wages or salaries earned often do not match the burden of the work done. Therefore, this is where unions or trade unions have an important role in meeting the interests of workers or workers in a company. Normatively, the provisions on trade unions or trade unions are applied in several laws and regulations in Indonesia, especially in Law No. 21 of 2000 concerning Trade Unions. Although there are also problems that surround it mainly because of the provision of the possibility of establishing some unions and allowed to accept donations from other countries. But the existence and current conditions make the existence of trade unions more widely accepted.